2020
DOI: 10.1111/febs.15179
|View full text |Cite
|
Sign up to set email alerts
|

BAX inhibitor‐1: between stress and survival

Abstract: Cellular gatekeepers are essential to maintain order within a cell and anticipate signals of stress to promote survival. BCL2 associated X, apoptosis regulator (BAX) inhibitor‐1 (BI‐1), also named transmembrane BAX inhibitor motif containing‐6, is a highly conserved endoplasmic reticulum (ER) transmembrane protein. Originally identified as an inhibitor of BAX‐induced apoptosis, its pro‐survival properties have been expanded to include functions targeted against ER stress, calcium imbalance, reactive oxygen spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 80 publications
0
25
0
Order By: Relevance
“…TMBIM6, also known as Bax inhibitor-1, is an inhibitor of Bax-mediated apoptosis ( 45 ). In cancers, TMBIM6 is regarded as a promoter of cancer progression.…”
Section: Discussionmentioning
confidence: 99%
“…TMBIM6, also known as Bax inhibitor-1, is an inhibitor of Bax-mediated apoptosis ( 45 ). In cancers, TMBIM6 is regarded as a promoter of cancer progression.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the protein of another gene recovered in the study, Apaf1 , acts downstream of Bax, and, along with Caspase-9, forms an apoptosome to induce apoptosis ( Figure 3 ) [ 37 ]. Interestingly, we also showed that Tmbim6 transcript levels are affected by BPA, and Tmbim6 was shown to inhibit Bax-induced apoptosis ( Figure 3 ) [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…TMBIM6 is highly conserved and ubiquitously expressed in humans, and has been shown to play a role in numerous cellular pathways including ER stress, calcium imbalance, reactive oxygen species accumulation, and metabolic dysregulation. More specifically, this protein is involved in cellular calcium and pH homeostasis by mediating Ca(2+) efflux from the ER, and functions to protect the cell from ER stress‐induced apoptotic cell death, although the exact molecular mechanism underlying this protein function is currently unclear 49‐51 . Altered TMBIM6 expression could dysregulate cellular response to stress, with interesting implications for AD susceptibility and progression.…”
Section: Discussionmentioning
confidence: 99%